2021
DOI: 10.1111/acel.13324
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of daf2 extends lifespan via tissue‐specific effectors that suppress distinct life‐limiting pathologies

Abstract: In aging Caenorhabditis elegans, as in higher organisms, there is more than one cause of death. C. elegans exhibit early death with a swollen, infected pharynx (P death), and later death with pharyngeal atrophy (p death). Interventions that alter lifespan can differentially affect frequency and timing of each type of death, generating complex survival curve shapes. Here, we use mortality deconvolution analysis to investigate how reduction of insulin/IGF‐1 signaling (IIS), which increases lifespan (the Age phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 45 publications
1
22
0
Order By: Relevance
“…Even if the maximal probability of making such a mistake is just one in 50 animals, the shift in accuracy for TLM is nearly ten times that of RSM, at 19.4 days compared to 20.07 days, respectively ( Figure 6E , Supplementary Table S3 ). This difference is exacerbated further when assaying long-lived animals, as just a 2% mis-scoring rate increasing from mid-life reduced median survival results from TLM by approximately two days when populations were generated from a distribution based on daf-2(e1370) lifespan characteristics (median 42 days, maximum 60 days ( Kenyon et al, 1993 ; Bansal et al, 2015 ; Hahm et al, 2015 ; Podshivalova et al, 2017 ; Zhao et al, 2021 )) ( Supplementary Figure S3 ). When the possibility of mis-scoring increases to a maximum of 10%, the TLM estimate dips to 17.34 days ( Figure 6E ).…”
Section: Resultsmentioning
confidence: 99%
“…Even if the maximal probability of making such a mistake is just one in 50 animals, the shift in accuracy for TLM is nearly ten times that of RSM, at 19.4 days compared to 20.07 days, respectively ( Figure 6E , Supplementary Table S3 ). This difference is exacerbated further when assaying long-lived animals, as just a 2% mis-scoring rate increasing from mid-life reduced median survival results from TLM by approximately two days when populations were generated from a distribution based on daf-2(e1370) lifespan characteristics (median 42 days, maximum 60 days ( Kenyon et al, 1993 ; Bansal et al, 2015 ; Hahm et al, 2015 ; Podshivalova et al, 2017 ; Zhao et al, 2021 )) ( Supplementary Figure S3 ). When the possibility of mis-scoring increases to a maximum of 10%, the TLM estimate dips to 17.34 days ( Figure 6E ).…”
Section: Resultsmentioning
confidence: 99%
“…In this study [118], two types of deaths have been reported in adult C. elegans: an early death with a swollen, infected pharynx and a later death with pharyngeal atrophy [118]. Interestingly, additional work analyzing some of the well-known long-lived C. elegans mutants, such as glp-1, eat-2, ced-1, and daf-2 mutant lines, revealed that these interventions change the frequency and/or timing of either form of death, thereby leading to an increase in lifespan [118][119][120]. Again, these observations in C. elegans are also in line with the notion that the rescue of one specific life-limiting pathology may be sufficient to explain lifespan extension.…”
Section: The "Hallmarks Of Aging"mentioning
confidence: 99%
“…In worms, age-related death has a multitude of causes: early death is associated with a swollen, infected pharynx and death later in life with pharyngeal atrophy. Loss-of-function daf-2 mutations decrease death caused by pharyngeal defects ( Zhao et al, 2021 ) and increase the mutant worms' resistance to colonisation by dietary bacteria ( Podshivalova et al, 2017 ). Cardiac-specific overexpression of dFOXO in Drosophila protects against loss of cardiac function during ageing ( Wessells et al, 2009 ).…”
Section: Single-gene Mutations That Extend Lifespanmentioning
confidence: 99%